Research on the Influence of Media Internalized Pressure on College Students’ Sports Participation—Chained Intermediary Analysis of Social Physique Anxiety and Weight Control Self-Efficacy - Ouyang, Yiyi; Luo, Jiong; Teng, Jinsheng; Zhang, Tingran; Wang, Kun; Li, Jing (Frontiers in Psychology, 2021)
Purpose: Discuss the relationship among college students’ media internalized pressure, social physique anxiety, weight control self-efficacy and sports participation to provide reference for promoting college students to develop healthy and confident living habits. Method: Take college students in western China as the object, select the subjects by stratified random sampling, and process the data with SPSS19.0 and AMOS21.0 statistical software. Results: 1) Media internalized pressure is positively correlated with social physique anxiety, weight control self-efficacy and sports participation; social physique anxiety is significantly positively correlated with weight control self-efficacy and sports participation, and weight control self-efficacy is significantly positively correlated with sports participation; 2) media internalized pressure has a direct effect on sports participation (ES= 0.456), social physique anxiety (ES=0.136) and weight control self-efficacy (ES=0.102) play a significant mediating role in the relationship between media internalized pressure and sports participation respectively, the chained mediating force of social physique anxiety and weight control self-efficacy also reaches a significant level (ES= 0.027). Conclusions: Media internalized pressure can influence college students' sports participation through direct path as well as indirect paths such as social physique anxiety, intermediary effect of weight control self-efficacy and chained intermediary effect of social physique anxiety - weight control self-efficacy, and social physique anxiety is another key factor affecting college students' sports participation except media internalized pressure.